BEBERAPA SIFAT FISIKA INCEPTISOL WATUTELA DALAM KAITANNYA DENGAN PEMBERIAN BAHAN ORGANIK DAN SUHU PEMANASAN - Jusman, Jusman; Widjajanto, Danang; Hasanah, Uswah (AGROTEKBIS, 2017)
This study aims to determine some physical properties Inceptisols Watutela in relation to organic matter and heating temperature. The research method is through laboratory experiments using completely randomized design (CRD), which consists of two factors. The first factor is the treatment of soil organic matter derived from goat droppings and the second factor is the heating temperature treatment. Each treatment consists of three levels and repeated 6 times to obtain         54 experimental units. Treatments organic matter goat manure include: without organic matter or Control (A0), organic matter with a level of 2.5% by weight of the ground (A1), and organic matter to the level of 5% of the weight of the soil used in the research (A2). Level-the level used in the heating temperature treatment includes heating at room temperature (P0), heating in an oven at a temperature of 50°C (P1) and heating it in an oven at 70°C (P2). Data processing studies to determine the effect of treatment among study done using ANOVA F test, subsequent treatment effect was tested further by honestly significant difference test (HSD). The research variables were observed consisting of: saturated soil water content, water content of field capacity, soil bulk density, soil porosity and soil aggregate stability. The results showed that the characteristics of Inceptisols Watutela the initial soil analysis showed a sandy loam texture, organic C content of 0.89% (relatively low). Based on observations showed that organic matter goat droppings and the heating temperature individually provide highly significant effect on all variables observed physical properties of soil. The interaction between organic material and the heating temperature very significant effect on saturated soil water content and soil porosity. On the other hand, the interaction between organic matter and heating temperature effect no significant effect on the measurement of field capacity moisture content, soil bulk density and soil aggregate stability Keywords: Inceptisol, Organic Material, Physical Properties Of Soil,Temperature